Trends in the training of project managers in Colombia: Review of the offer at the level of specializations (2021)
The purpose of this work was to investigate the offer of specialization programs in project management in Colombia, which allowed to characterize the offer, the study plans, the courses included in their curricular networks and the main coincidences between these programs. Additionally, the training trend in the discipline, its relationship with the geographical area where it is offered and the degree of alignment of the Colombian offer with training worldwide, was identified.